1996
DOI: 10.1002/(sici)1096-9888(199608)31:8<831::aid-jms392>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfer Reactivity of Large Multiply Charged Ions

Abstract: Charge-charge interactions dramatically influence the dissociation and proton transfer reactivity of large multiply protonated ions. In combination with tandem mass spectrometry, proton transfer reactions have been used to determine the charge state of an ion and to increase the effective mass resolution of electrospray ionization mass spectra. A model for the proton transfer reactivity of multiply protonated ions, in which protons are assigned to specific sites in an ion based on the intrinsic reactivity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
187
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 186 publications
(194 citation statements)
references
References 54 publications
7
187
0
Order By: Relevance
“…The former process can result in charge reduction of the analyte or metal ion species via proton transfer to solvent [31,36,37]. The ESI mass spectra of the trivalent hydrated metal ions are very sensitive to source conditions.…”
Section: Mechanism Of Ion Formation: Solvent Evaporation Versus Condementioning
confidence: 99%
“…The former process can result in charge reduction of the analyte or metal ion species via proton transfer to solvent [31,36,37]. The ESI mass spectra of the trivalent hydrated metal ions are very sensitive to source conditions.…”
Section: Mechanism Of Ion Formation: Solvent Evaporation Versus Condementioning
confidence: 99%
“…As discussed previously [36,39], it is impossible to calculate the total ion energy for all possible charge site assignments for each structure [20a, 36]. Here, we assume formal charges of ϩ3 on the heme iron atom and -1 on each heme carboxylate group [12,40] Added protons from the electrospray process are confined to basic Arg, His, or Lys residues.…”
Section: Charge Placement In Simulated Structuresmentioning
confidence: 99%
“…However, an understanding of the relationship between gas phase structure and solution conformation is still at a very primitive stage, in large part because detailed gas phase structural information is limited. In addition to chemical probes of gas phase ion structure [1][2][3][4][5][6][7][8][9][10][11][12][13][14], a number physical methods are being developed to examine gas-phase peptide and protein ion structure [15][16][17][18][19][20][21][22][23][24][25][26][27], including collisional activation to examine fragmentation pathways [18 -23, 25-27]. A few studies have suggested that ion conformation may influence fragmentation pathways [19,23,27,28].…”
mentioning
confidence: 99%